Pengukuran Penerimaan Aplikasi e-Coklit Berdasarkan Persepsi PPK, PPS, dan Pantarlih Menggunakan Technology Acceptance Model - Ego Saputra; Kurniawan Zaini (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The 2024 ELECTION is a big event that involves many officers as event organizers, including PPK, PPS, and Pantarlih. Citizen data collection activities as prospective voters throughout Indonesia have various problems that are quite complicated, so there is a need for a system in the form of an application that helps simplify and expedite the data collection process. The application that is applied is E-Coklit. The e-Coklit application contains many opinions among users; for this reason,n it is necessary to analyze the perceptions of application users. This study aims to measure the acceptance of e-cockpit applications based on user perceptions based on the instruments used in the Technology Acceptance Model (TAM). The method used is a quantitative research method, based on the variables EOU (Ease of Use), UO (Usefullnes of Use), BIU (Behavioral Intention to Use), and ATU (Attitude toward using) as independent variables and ASU (Actual System of Use) is a variable dependent. Based on the results of the analysis test, it can be concluded that the use of the E-Coklit application for citizen data collection as prospective voters in the 2024 ELECTIONS fulfils the criteria because it can simplify and expedite officer activities so that they are more effective and efficient.